Loop-mediated isothermal amplification for Rickettsia typhi (the causal agent of murine typhus): Problems with diagnosis at the limit of detection - Dittrich, S; Castonguay-Vanier, J; Moore, C; Thongyoo, N; Newton, P; Paris, D (2014)
Murine typhus is a flea-borne disease of worldwide distribution caused by Rickettsia typhi. Although treatment with tetracycline antibiotics is effective, treatment is often misguided or delayed due to diagnostic difficulties. As the gold standard immunofluorescence assay is imperfect, we aimed to develop and evaluate a loop-mediated isothermal amplification (LAMP) assay. LAMP assays have the potential to fulfill the WHO ASSURED criteria (affordable, sensitive, specific, user friendly, robust and rapid, equipment free, deliverable to those who need them) for diagnostic methodologies, as they can detect pathogen-derived nucleic acid with low technical expenditure. The LAMP assay was developed using samples of bacterial isolates (n=41), buffy coat specimens from R. typhi PCR-positive Lao patients (n=42), and diverse negative controls (n=47). The method was then evaluated prospectively using consecutive patients with suspected scrub typhus or murine typhus (n=266). The limit of detection was ∼40 DNA copies/LAMP reaction, with an analytical sensitivity of<10 DNA copies/reaction based on isolate dilutions. Despite these low cutoffs, the clinical sensitivity was disappointing, with 48% (95% confidence interval [95% CI], 32.5 to 62.7%) (specificity, 100% [95% CI, 100 to 100%]) in the developmental phase and 33% (95% CI, 9.2 to 56.8%) (specificity, 98.5% [95% CI, 97.0% to 100%]) in the prospective study. This low diagnostic accuracy was attributed to low patient R. typhi bacterial loads (median, 210 DNA copies/ml blood; interquartile range, 130 to 500). PCR-positive but LAMP-negative samples demonstrated significantly lower bacterial loads than LAMP-positive samples. Our findings highlight the diagnostic challenges for diseases with low pathogen burdens and emphasize the need to integrate pathogen biology with improved template production for assay development strategies. Copyright © 2014 Dittrich et al.